Kinetika Reaksi Etanolisis Minyak Jarak Dengan Katalisator Kalium Hidroksid Dalam Sebuah Reaktor Alir Tangki Berpengaduk = Kinetics of Ethanolysis of Castor Oil Using Potassium Hydroxide as Catalyst in A Continuous Stirr - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT In a lot of researches on alcoholysis of castor oil and other vegetable oils, the steps of mono- and diglycerides formation on reaction rate were not considered. The reaction was evaluated with the assumption that all of the three fatty acid groups in a glyceride molecule were attacked by ethanol at the same time. This research would verify that the reaction of the three fatty acid groups proceeds step by step. Four kinetics models of ethanolysis of castor oil were then established based on the reaction steps of the fatty acid groups. The ethanolysis of castor oil using potassium hydroxide as catalyst was initiated by heating castor oiI in a tank flow reactor equipped with initial ethanol feed heater, peristaltic pumps, rotameters, condenser, mechanical stirrer, digital thermometer, product withdrawal, and a water bath. At the same time, ethanol containing potassium hydroxide was heated in another vessel. As soon as the reaction temperature was reached, the, two reactants were quickly mixed. Afterwards, the castor oil and the ethanol containing the catalyst were pumped into the reactor continuously, and the product was constantly withdrawn. The glycerol concentration in the product was analyzed spectrophotometrically until steady state condition was reached. Then, the concentration of glycerol at steady state condition was reanalyzed using acetin method, while ethyl ricinoleate concentration was indirectly determined by measuring the increase of the hydroxyl groups in the glyceride using a method for determination of acetyl value. The data obtained were glycerol and ethyl ricinoleate concentrations in the product of various residence time and catalyst concentrations. The ratio of the ethyl ricinoleate formed to the glycerol produced was greater than three. This proved that the reaction of fatty acid groups in castor oil ethanolvsis proceeded in steps. The reaction rate constant of the secondary group was somewhat greater than those of the primary groups. Hence, it was apparent that the secondary fatty acid group was a bit more reactive than the primary ones. Furthermore, based on the analysis of the effect of catalyst concentration on the reaction rate constants for the primary and secondary groups, it could be concluded that the kinetics model assuming step by step attack on the fatty acid groups (model In) was the most logically acceptable model among the four models proposed.